Measuring dynamic process of working memory training with functional brain networks - Wang, Hong (EAI Endorsed Transactions on Ambient Systems, 2016)
In this paper, we proposed the functional brain networks and graphic theory method to measure the effect of working memory training on the neural activities. 12 subjects were recruited in this study, and they did the same working memory task before they had been trained and after training. We architected functional brain networks based on EEG coherence and calculated properties of brain networks to measure the neural co-activities and the working memory level of subjects. As the result, the internal connections in frontal region decreased after working memory training, but the connection between frontal region and top region increased. And the more small-world feature was observed after training. The features observed above were in alpha (8-13 Hz) and beta (13-30 Hz) bands. The functional brain networks based on EEG coherence proposed in this paper can be used as the indicator of working memory level.